The Urgency of Financial Literacy in Financial Management in Generation Z in the Society 5.0 Era - Anwar, Syamsul; Ali, Ali; Widiastuti , Anna (Raudhah Publisher, 2024)
The era of society 5.0 which has a tendency or contains everything about the use of technology and communication has had a good impact on the development of digital-based business. When this large digital base is not balanced with good financial literacy, it will also have quite a bad impact. One generation that is considered to have a high consumerist attitude is generation Z. Therefore, there is a need for comprehensive reading and understanding regarding financial literacy, which then has implications for good financial management.